New Protoribates (Acari, Oribatida, Haplozetidae) from Vietnam - Ermilov, Sergey G.; Starý, Josef (Zootaxa, 2017)
Three new species of oribatid mites of the genus Protoribates (Oribatida, Haplozetidae) are described based on adult specimens from the Tam Dao National Park of Northern Vietnam. Protoribates chistyakovi sp. nov. differs from P. sangumburiensis (Choi, 1996) by being larger, the localization of lamellar setae, and morphology of rostrum and interlamellar setae. Protoribates shaldybinae sp. nov. differs from P. dentatus (Berlese, 1883) by its distinctly foveolate body surface, morphology of pedotecta II and leg tarsi I and II, and much longer adanal setae ad2. Protoribates shvanderovi sp. nov. differs from P. gracilis (Aoki, 1982) by its larger body size, localization of lamellar setae, and the relative lengths of lamellar, interlamellar and bothridial setae, and longer dorsophragmata. An identification key to the Vietnamese species of the genus Protoribates is given.